Comments on "Dredging in an estuary causes contamination by fluid mud on a tourist ocean beach. Evidence via REE ratios" by N. Mirlean, L. Calliari, and K. Johannesson in Marine Pollution Bulletin 159 (2020) 111495. https://doi.org/10.1016/j.marpolbul.2020.111495. (May 2021) - Garcia, Carlos Alberto Eiras; Evangelista, Heitor; Möller, Osmar Olinto
Abstract: N. Mirlean, L. Calliari, and K. Johannesson examined the REE paired La/Eu and Gd/Yb ratios in the region of Patos Lagoon estuary/Brazil and related coastal waters. They concluded that " the mud deposition events at the beach were most likely associated with dredging processes in the estuary especially where overflow is the source of fluid mud on the beach shoreface ". In this response to that study, we reflect on several discrepancies in their methods, results and conclusions. In this work, we demonstrate that the approach adopted by the authors does not provide evidence that the selected REE ratios measured on muddy deposits on the beach were derived from dredged activities, particularly regarding overflow. On the contrary, based on their results, the REE ratios presented in the suspended sediments collected in the navigation channel are most likely associated to natural sediments.